Odpowiedź :
Odpowiedź:
1. [tex]\frac{3^{10} * 2^{8} }{2^{6} } * \frac{2^{3} }{3^{5} }[/tex]
2. [tex]3^{5} * 2^{2} * 2^{3}[/tex]
3. [tex]6^{5}[/tex]
[tex]\dfrac{3^{14}\cdot2^{8}}{3^{4}\cdot(2^{3})^{2}}:\dfrac{3^{5}}{2^{3}} = \dfrac{3^{14}\cdot2^{8}}{3^{4}\cdot2^{6}}\cdot\dfrac{2^{3}}{3^{5}} =\dfrac{3^{14}\cdot2^{11}}{3^{9}\cdot2^{6}}=3^{5}\cdot2^{5} = (3\cdot2)^{5} = 6^{5}[/tex]
Wyjaśnienie:
Korzystamy z własności potęg:
[tex]a^{m}\cdot a^{n} = a^{m+n}\\\\a^{m}:a^{n} = a^{m-n}\\\\(a^{m})^{n} = a^{m\cdot n}[/tex]